COVID-19: analysis of the risks of operating during the pandemic. What are the real perioperative complications in asymptomatic patients and how to optimize early diagnosis? - Thaís de Sousa Gonçalves; Bruna Lago Chaves; Lia Patrus Bannet; Sergio Carreirão; Farid Hakme (Revista Brasileira de Cirurgia Plástica, 2020)
Introduction: Controlling dissemination as well as treating patients infected with the new coronavirus are global challenges. Despite the protocols and guidelines generated by the WHO and the leading medical societies that seek to control the pandemic, there are still few reports in the literature that show complications in the perioperative period of patients, initially asymptomatic, infected by COVID-19. This study aims to offer data to plastic surgeons beyond the scope of aesthetic and reconstructive surgeries. Methods: A review article was performed after selecting sixteen articles from PubMed. These were analyzed for their type, statistical relevance, number of participants, complications, and reported outcomes. Results: The mortality rate of patients with COVID-19 undergoing surgical procedures was higher than that estimated in infected patients who did not undergo these procedures. There were also increases in the patient's admission rate to intensive care units and the pulmonary complications rate. The main predictors of mortality were defined, besides the role of chest tomography for the diagnosis of COVID-19 in the perioperative period. Conclusion: It is essential to understand the risk of operating patients during the pandemic, even if asymptomatic. The increased risk of complications and mortality in elective and emergency surgeries requires disseminating adequate information to both doctors and patients. The objective, therefore, is not to define the medical conduct of surgeons, but to allow analysis in the decision-making process.